The 2010 14th International Conference on Computer Supported Cooperative Work in Design 2010
DOI: 10.1109/cscwd.2010.5471998
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and pressing: A formula for teamwork — A case study

Abstract: The software industry has recognized the importance of teamwork as a driver for good projects results. However teamwork is not an easy goal to reach, because there is a large list of variables affecting the process. Each project probably will require a particular recipe to promote and perform real teamwork. Therefore a one-size fits-all approach does not work to promote teamwork in the software development scenarios. This article presents an influence model that helps the development teams to find a strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, based on an analysis of 27 software projects done with students, Marques et al [2010] reported that pressure acts as a support that triggers teamwork. "Pressing" is induced with deadline pressures with coordination by the teaching staff.…”
Section: Effect On Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, based on an analysis of 27 software projects done with students, Marques et al [2010] reported that pressure acts as a support that triggers teamwork. "Pressing" is induced with deadline pressures with coordination by the teaching staff.…”
Section: Effect On Individualsmentioning
confidence: 99%
“…Group interaction [Langer et al 2014;Lohan et al 2014;Marques et al 2010;Maruping et al 2015;Park et al 2008] Other Fields other than Software Engineering and Information Systems [Borg 2014;Clegg et al 1996;Fujigaki 1996;Fujigaki and Mori 1997;Jemielniak 2009;Perlow 1998Perlow , 1999Perlow , 2001Sawyer and Southwick 2002;Staudenmayer et al 2002;Tapia 2004 Well-being [Fujigaki 1996;Fujigaki and Mori 1997;Graziotin et al 2017;Laanti 2013;Tuomivaara et al 2017] In further work, Ebert and Jones [2009] noted that projects with higher defect removal effectiveness tend to have shorter schedules, as testing is the part of development where delays typically happen. This observation is supported by Table 4 that showed a high number of papers in the quality assurance phase.…”
Section: Causes Of Time Pressurementioning
confidence: 99%